2018
DOI: 10.3847/1538-4357/aa9ff5
|View full text |Cite
|
Sign up to set email alerts
|

Warm Dark Matter and Cosmic Reionization

Abstract: In models with dark matter made of particles with keV masses, such as a sterile neutrino, small-scale density perturbations are suppressed, delaying the period at which the lowest mass galaxies are formed and therefore shifting the reionization processes to later epochs. In this study, focusing on Warm Dark Matter (WDM) with masses close to its present lower bound, i.e. around the 3 keV region, we derive constraints from galaxy luminosy functions, the ionization history and the Gunn-Peterson effect. We show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 81 publications
1
31
0
Order By: Relevance
“…Previous works have studied the effect of non-CDM models on the 21-cm signal [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Those models typically suppress the matter power spectrum beyond some wavenumber k, delaying the onset of cosmic dawn.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have studied the effect of non-CDM models on the 21-cm signal [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Those models typically suppress the matter power spectrum beyond some wavenumber k, delaying the onset of cosmic dawn.…”
Section: Introductionmentioning
confidence: 99%
“…WDM predicts fewer low-mass galaxies than CDM, with a larger difference at high redshift. For our choice of warm candidate mass (3 keV), the relative difference between CDM and WDM is only a factor of a few stellar masses around 10 6 M (see also Villanueva-Domingo et al 2018), below what is currently observable (Bouwens et al 2015(Bouwens et al , 2017Ceverino et al 2017). On the other hand, our results are in agreement with Corasaniti et al (2017), who found a lower limit of 2 keV from analysis of the luminosity function.…”
Section: Stellar Mass Functionmentioning
confidence: 94%
“…Future observations and facilities might improve this limit (e.g. JWST ), but then a very careful understanding of the baryonic physics implemented in the simulations will be needed, as discussed in Villanueva-Domingo et al (2018).…”
Section: Stellar Mass Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also refer readers to Ref. [165][166][167][168][169][170][171][172][173][174][175][176][177][178][179] for hydrodynamical simulation results differentiating WDM and CDM in galaxy formation. We estimate the observed number of satellites above M = 10 8 h −1 M as N obs sat = 63 (11 classical dwarf galaxies and 3.5 × 15 ultra-faint dwarf galaxies).…”
Section: )mentioning
confidence: 99%